2023
DOI: 10.3389/fbioe.2023.1192720
|View full text |Cite
|
Sign up to set email alerts
|

Low-intensity pulsed ultrasound regulates osteoblast-osteoclast crosstalk via EphrinB2/EphB4 signaling for orthodontic alveolar bone remodeling

Abstract: Background: The limited regenerative potential of periodontal tissue remains a challenge in orthodontic treatment, especially with respect to alveolar bone remodeling. The dynamic balance between the bone formation of osteoblasts and the bone resorption of osteoclasts controls bone homeostasis. The osteogenic effect of low-intensity pulsed ultrasound (LIPUS) is widely accepted, so LIPUS is expected to be a promising method for alveolar bone regeneration. Osteogenesis is regulated by the acoustic mechanical eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…The effect of LIPUS on accelerating tooth movement may be attributed to its promotion of osteoclast differentiation (Trackman et al, 2013;Feres et al, 2016;Zhou et al, 2023). In this study, LIPUS enhances osteoclastic differentiation and accelerates OTM from the third day, which is consistent with other research (Zhou et al, 2023).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The effect of LIPUS on accelerating tooth movement may be attributed to its promotion of osteoclast differentiation (Trackman et al, 2013;Feres et al, 2016;Zhou et al, 2023). In this study, LIPUS enhances osteoclastic differentiation and accelerates OTM from the third day, which is consistent with other research (Zhou et al, 2023).…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, several animal experiments showed that LIPUS could accelerate tooth movement in rats ( Trackman et al, 2013 ; Alazzawi et al, 2018 ; Arai et al, 2020 ). The effect of LIPUS on accelerating tooth movement may be attributed to its promotion of osteoclast differentiation ( Trackman et al, 2013 ; Feres et al, 2016 ; Zhou et al, 2023 ). In this study, LIPUS enhances osteoclastic differentiation and accelerates OTM from the third day, which is consistent with other research ( Zhou et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In vivo , the rats under anesthesia were placed at a constant location, after which the transducer was pressed against the side of the cheek closest to the maxillary first molar. In vitro , we attached the transducer to the bottom of the plate corresponding to the well[ 18 ].…”
Section: Methodsmentioning
confidence: 99%